Wspólnota rodzinna w korespondencji prywatnej Marii Konopnickiej (z antroponomastykonu familiolektu) - Wiatrowski, Przemysław (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2025)
This article examines the family correspondence of Maria Konopnicka. Its aim is to analyze personal proper names appearing in 843 letters written by the poet to her closest family members: her husband, children, sons-in-law, daughter-inlaw and uncle. The research material includes over 140 anthroponyms – given names, surnames and nicknames – used exclusively to identify members of Konopnicka’s family. The given names and surnames occur in their formal forms or are morphologically modified. Formal transformations are also noticeable within nicknames. The structural modifications applied by the author intensify the expressive character of the names. A similar effect is achieved by augmenting the anthroponyms with evaluative-emotional descriptions, most often with a positive connotation. Negative emotions are signaled by reducing the names of her husband and one of her daughters to initials. The writer’s correspondence also confirms the practice of naming women and married couples using derivatives based on the husband’s name. The anthroponyms present in Konopnicka’s family language perform functions that are delimitative, phatic, appellative, stimulating, cognitive and evaluative-expressive in nature.